2017
DOI: 10.1093/toxsci/kfx133
|View full text |Cite
|
Sign up to set email alerts
|

From the Cover: Lifelong Exposure of C57bl/6n Male Mice to Bisphenol A or Bisphenol S Reduces Recovery From a Myocardial Infarction

Abstract: Bisphenol A (BPA) leaches from plastics to contaminate foodstuffs. Analogs, such as bisphenol S (BPS), are now used increasingly in manufacturing. Greater BPA exposure has been correlated with exacerbation of cardiovascular disease, including myocardial infarction (MI). To test the hypothesis that bisphenol exposure impairs cardiac healing, we exposed C57bl/6n mice to water containing 25ng/ml BPA or BPS from conception and surgically induced an MI in adult male progeny. Increased early death and cardiac dilati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 57 publications
3
19
0
Order By: Relevance
“…The presence of CCR2 + macrophages, together with reduced myocardial vascularization, may be indicative of defective reparative processes. In agreement with our results, chronic administration of BPA or its substitute, Bisphenol S (BPS), can reduce active cardiac remodeling in response to myocardial infarction, increasing metalloproteinase (MMP) expression in male mice 12 . Moreover, the exposure of resting monocytes to BPA increased polarization to activated macrophages 64 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The presence of CCR2 + macrophages, together with reduced myocardial vascularization, may be indicative of defective reparative processes. In agreement with our results, chronic administration of BPA or its substitute, Bisphenol S (BPS), can reduce active cardiac remodeling in response to myocardial infarction, increasing metalloproteinase (MMP) expression in male mice 12 . Moreover, the exposure of resting monocytes to BPA increased polarization to activated macrophages 64 .…”
Section: Discussionsupporting
confidence: 89%
“…Recently, it has been reported that a life long exposure to BPA in rodents produces arrhythmogenic effects 11 . Moreover, it has been demonstrated that acute or chronic exposure to BPA, impaired functional recovery after myocardial infarction due to a reduced ability to induce macrophage polarization from proinflammatory to a reparative state 12,13 . Indeed, there is an increasing concern about BPA higher bioaccumulation in developing organisms and special vulnerable populations such cell cultures.…”
mentioning
confidence: 99%
“…BPA preferentially binds ERβ over ERα but the metabolized forms of BPA, such as BPA glucuronide, do not bind the ERs (28). Epidemiological and animal data indicate that increased exposure to BPA worsens cardiovascular diseases including hypertension (3133), atherosclerosis (3436), myocardial infarct (37), arrhythmias (13, 14), and DCM (38). To our knowledge, no one has examined the role of BPA on myocarditis.…”
Section: Introductionmentioning
confidence: 99%
“…13 who suggested a conflict of interest in the form of chemical industry funding. In mouse models of myocardial infarctions several studies found chronic BPA exposure worsened outcomes 1416 . Furthermore, laboratory animal studies consistently show acute 5,17 and life-long 18,19 exposure of BPA at doses within the ranges seen in human populations has pro-arrhythmic effects.…”
Section: Introductionmentioning
confidence: 99%
“…A study examining individuals from the United States and 7 Asian countries detected BPS in 81% of urine samples with an average concentration of 2.6 nM, suggesting widespread exposure 23 . Of significant concern is the finding that acute BPS exposure shows a similar pro-arrhythmic effect 21 and impairment of post-myocardial infarction recovery 14 as BPA. Chronic exposure of BPS to zebrafish larvae induce developmental deformities in a number of organs including the heart 24,25 .…”
Section: Introductionmentioning
confidence: 99%